Innovative use of biowaste based cementitious grouts for semi-flexible pavement application and optimization using response surface methodology - Muhammad Imran Khan (PLoS ONE, 2025)
This study investigates the potential usage of biowaste (i.e., bagasse ash) in cementitious grouts for semi-flexible pavement applications. Cementitious grouts were prepared by partially replacing cement with bagasse ash (5%, 10%, 15% and 20%) and at w/c ratios of 0.30 to 0.40. Flow cone apparatus was used to determine the flow properties of fresh cementitious grouts. The hardened specimens of cementitious grouts also were tested for compressive strength at curing ages of 7 and 28 days. Moreover, response surface methodology (RSM) was used to analyze the relationships between independent/input variables (bagasse ash and w/c ratio) and dependent/output variables (flow and compressive strength). Compressive strength tests revealed that 7-day strength ranged from 27 MPa to 41 MPa, while 28-day strength ranged from 35 MPa to 65 MPa. Results indicate that bagasse ash significantly influences the flowability and compressive strength of the cementitious grouts, with optimal performance achieved at a 15% replacement level and a 0.35 w/c ratio. The optimal combination achieved a flow value of 16 seconds, a 7-day compressive strength of 32 MPa, and a 28-day compressive strength of 49 MPa. Response surface methodology (RSM) confirmed these results, identifying an optimized mix composition of 16% bagasse ash and a 0.35 w/c ratio. The findings demonstrate the potential of bagasse ash as a sustainable alternative to cement, contributing to reduced environmental impact and improved material performance in semi-flexible pavements.